2006
DOI: 10.1016/j.molcel.2006.04.014
|View full text |Cite
|
Sign up to set email alerts
|

A Short Mitochondrial Form of p19ARF Induces Autophagy and Caspase-Independent Cell Death

Abstract: The tumor suppressor functions of p19(ARF) have been attributed to its ability to induce cell cycle arrest or apoptosis by activating p53 and regulating ribosome biogenesis. Here we describe another cellular function of p19(ARF), involving a short isoform (smARF, short mitochondrial ARF) that localizes to a Proteinase K-resistant compartment of the mitochondria. smARF is a product of internal initiation of translation at Met45, which lacks the nucleolar functional domains. The human p14(ARF) mRNA likewise prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
247
4
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(271 citation statements)
references
References 38 publications
18
247
4
2
Order By: Relevance
“…Assessing cell death by this assay was consistent with other more traditional and less accurate cell death assays, such as Trypan blue exclusion tests. 11 It is noted that the luminescence values are linear over several orders of magnitude, providing a wide window of detection of viable cells (between 10 2 and 10 5 cells; Supplementary Figure S4a). Moreover, every point in each experiment is tested in 10 replicates, thus conferring a high degree of Figure 1 A platform to analyze the PCD network, which combines quantitative assessment of cell death, molecular responses, and computational approaches for novel pathway discovery.…”
Section: Resultsmentioning
confidence: 99%
“…Assessing cell death by this assay was consistent with other more traditional and less accurate cell death assays, such as Trypan blue exclusion tests. 11 It is noted that the luminescence values are linear over several orders of magnitude, providing a wide window of detection of viable cells (between 10 2 and 10 5 cells; Supplementary Figure S4a). Moreover, every point in each experiment is tested in 10 replicates, thus conferring a high degree of Figure 1 A platform to analyze the PCD network, which combines quantitative assessment of cell death, molecular responses, and computational approaches for novel pathway discovery.…”
Section: Resultsmentioning
confidence: 99%
“…Only a few examples are available to prove that autophagy is an important death pathway in cells with intact apoptosis machinery. 28 On the basis of several indirect evidences it has been proposed that active cell death is induced through autophagy in tamoxifen-treated MCF-7 cells; 5 one of the evidences is the inhibition of both autophagy and cell death by 3-MA, a compound that can specifically block the sequestration step in macro-autophagocytosis inhibiting class III phosphatidylinositol-kinase activity. As in our experiments 3-MA also inhibited macrophage and MCF-7 cell-mediated phagocytosis of dying de novo autophagic cells, it can be suggested that molecular events linked to autophagy and death are involved in specific surface changes, which are important in subsequent recognition and elimination of these dying cells.…”
Section: Discussionmentioning
confidence: 99%
“…A short form ARF, designated smARF, can be generated by internal initiation of translation. 29 This short form of ARF is translocated to the mitochondria and triggers caspaseindependent cell death. Cell death is attenuated when the expression of ATG5 and BECN1 is knocked down by siRNA.…”
Section: Cell Death (Apoptosis)mentioning
confidence: 99%